2015
DOI: 10.1097/mao.0000000000000552
|View full text |Cite
|
Sign up to set email alerts
|

Calvarium Thinning in Patients with Spontaneous Cerebrospinal Fluid Leak

Abstract: Patients with spontaneous CSF leak are more likely to be obese, have the diagnosis of OSA, and show thinning of their entire calvarium that is independent of BMI. These data suggest an additional obesity-associated intracranial process contributes to skull thinning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
103
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(110 citation statements)
references
References 13 publications
6
103
1
Order By: Relevance
“…This is not surprising, because both superior canal dehiscence and spontaneous CSF fistula are characterized by a thin tegmen . Nelson et al demonstrated patients with spontaneous CSF fistula have thinner temporal bone squamosa than a control group of patients who underwent cochlear implantation . Whyte et al showed a similar relationship of a thin tegmen in patients with superior canal dehiscence .…”
Section: Discussionmentioning
confidence: 98%
“…This is not surprising, because both superior canal dehiscence and spontaneous CSF fistula are characterized by a thin tegmen . Nelson et al demonstrated patients with spontaneous CSF fistula have thinner temporal bone squamosa than a control group of patients who underwent cochlear implantation . Whyte et al showed a similar relationship of a thin tegmen in patients with superior canal dehiscence .…”
Section: Discussionmentioning
confidence: 98%
“…This process may be expedited, or possibly congenital, in patients with low and/or thin skull bases (especially superior canal dehiscence syndrome [SCDS] patients) . Although a rapidly expanding body of literature has been devoted to this phenomenon over the past 2 decades, objective links between ICP, LPOP, and skull base thickness are currently lacking …”
Section: Specific Roles For the Otolaryngologistmentioning
confidence: 99%
“…Many of the reports did not correlate the severity of OSA with polysomnography, nor was it offered to patients with OSA symptoms (snoring, excessive daytime sleepiness, and fatigue). [6][7][8]11 The lack of formal polysomnograms in all patients with spontaneous CSF leaks may have underestimated the incidence of OSA.…”
Section: Discussionmentioning
confidence: 97%
“…There was no difference in the skull thickness of patients with a spontaneous CSF leak and OSA compared with those with a spontaneous CSF leak without OSA. Fleischman et al 11 Nelson et al 8 Three published studies were included in the analysis: LeVay and Kveton, 6 Nelson et al, 8 and Fleischman et al 11 OR indicates odds ratio of bias; SE, standard error …”
Section: Summary Of Literature Search and Meta-analysismentioning
confidence: 99%